TINJAUAN YURIDIS SERTA PERAN MASYARAKAT DAN KOMISI PEMILIHAN UMUM DALAM MENGATASI POLITIK UANG (MONEY POLITIK) DI PEMILIHAN UMUM - Imam Rahmaddani (Fakultas Hukum Universitas Islam Syekh Yusuf, 2022)
In general, money politics fits into a transactional political pattern, in which votes are exchanged for goods or services. This study aims to study and analyze the legal provisions governing money politics, the role of the public and the KPU in fighting money politics, and the impact of money politics on Indonesian democracy. Subject selection, data tracking, determining research focus, collecting data sources, presenting data, and compiling reports are the steps in this research process. In this study, documentation was used to collect data by finding data about the variables studied in papers, journals and reports. Content analysis is used to analyze data, which can be cross-checked based on context. Law Number 10 of 2016 and Law Number 1 of 2015 prohibit political parties or coalitions of political parties from receiving compensation in any form during the nomination process for governor, mayor or regent. Keywords: Regulation; Public; KPU; Money politic.